IMPACT OF HEDONIC AND UTILITARIAN SHOPPING MOTIVE ON ONLINE PURCHASE DECISION - DR.A.VARADARAJ; Mrs.D.CHARUMATHI (CSIE Working Papers Series, 2019)
The change in technological area all over the world has changed the concept of information and communication. The use of internet for commercial purposes gave rise to the existence of the electronic commerce (e-commerce) phenomenon. Online shopping or e-shopping is a form of electronic commerce which allows consumers to directly buy goods or services from a seller over the Internet using a web browser. The study focuses on the impact of hedonic and utilitarian motives on the consumers buying behaviour towards online shopping. Questionnaire was used to collect the primary data. The sample size of the study was 125 and the sample design adopted was convenience sampling. This paper tried to find out the impact of hedonic and utilitarian motive on the consumer buying behaviour towards online shopping and gives suggestions to improve the same.